Finanças públicas na nova ordem constitucional brasileira: uma análise comportamental dos municípios potiguares, nos anos antecedentes e posteriores à lei de responsabilidade fiscal LRF - Silva, William Gledson e (2009)
The object of the present dissertation is to analyze the behavior of the public finances of the districts of the state of Rio Grande do Norte (RN), taking as reference a period fundamentally previous to the implementation of the Fiscal Responsibility Law LRF, comparatively to the first years, immediately after the advent of the mentioned institutional milestone. The central hypothesis of this study proposes that, from the institutions' viewpoint, the LRF sets securely consistent rules, in the orchestration of the behavior of the municipal revenues and expenses. These regulations, on the other hand, might be effective and reach the districts of the RN indiscriminately, apart from stabilizing tendencies and which are sustainable in the long run. In spite of this, the indicators calculated reveal that the districts researched show, during all the period under analysis, a diminished capacity of self-tax collection , and consequently, a high participation of the intergovernmental transfers in the composition of the current revenues. This behavior indicates that the goal of strengthening the municipal public finances, forecast in the LRF, tends to be only partially accomplished, due to the fiscal decentralism. The analysis and interpretation of the data are conducted from the literature of institutionalist orientation and in descriptive statistical tools applied to the municipal strata of the state of Rio Grande do Norte. Further on, it's used the econometrical method Pooled OLS, which demands the elimination of the municipal strata in order to allow the use of the model, in the attempt to strengthen and/or ratify the results of the research. Finally, the evidence reached in the dissertation show that the LRF brings better conditions to the potiguar municipal public finances, predominantly to the economically stronger districts; whereas the less dynamic municipal entities show rather divergent evidence, that is, their economies seem to be more oriented to a more pronounced state participation; therefore, it generates in the state of RN a certain antithesis in the results reached in the dissertation